2022
DOI: 10.2460/javma.21.10.0439
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel helical fan beam imaging system for computed tomography of the distal limb in sedated standing horses: 167 cases (2019–2020)

Abstract: OBJECTIVE To evaluate the diagnostic capabilities of a novel helical fan beam CT system used for imaging of horses with a range of clinical distal limb problems. ANIMALS 167 horses. PROCEDURES Medical records were reviewed of horses presented for CT of the distal limb at 2 university-based veterinary hospitals. The following data were recorded: age, sex, breed, presenting complaint, sedation used for imaging, scanning time, procedure time, other diagnostic imaging methods performed, imaging diagnosis, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
(104 reference statements)
0
24
0
Order By: Relevance
“…We did find that slight motion could obscure the detail of head structures easily, such that a repeated scan was more often needed when imaging the head and neck, compared with imaging the distal limbs. 20 IV and intra-arterial contrast enhancement techniques have been described for horses. 3,21,22,39 The IV technique uses more contrast medium than the intra-arterial technique, because the contrast medium is diluted before reaching the location of interest, but the contrast enhancement obtained with the 2 techniques is similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did find that slight motion could obscure the detail of head structures easily, such that a repeated scan was more often needed when imaging the head and neck, compared with imaging the distal limbs. 20 IV and intra-arterial contrast enhancement techniques have been described for horses. 3,21,22,39 The IV technique uses more contrast medium than the intra-arterial technique, because the contrast medium is diluted before reaching the location of interest, but the contrast enhancement obtained with the 2 techniques is similar.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of this CT system for imaging of the distal limbs in horses has been described. 20 The objective of the retrospective study reported here was to evaluate the diagnostic capabilities of the Equina system when used for imaging of horses with clinical problems of the head and neck.…”
mentioning
confidence: 99%
“…Other non-invasive imaging methods such as MRI, nuclear imaging, and infrared spectroscopy are able to detect lesions and abnormalities before the onset of gross disease [ 8 , 9 , 33 , 34 , 35 , 36 ]. Recently, a commercial option has been proposed for obtaining CT images in anesthetized standing horses [ 7 ]. Whether such systems can provide texture features of the PSBs comparable with μCT and whether those features could be used for modeling the risk of catastrophic injury remains in question.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining CT images of the horses under load bearing conditions is challenging as general anesthesia is required for compliance and to minimize the risk of motion artifacts. Some technical advances in standing CT have been suggested but whether these devices can achieve sufficient spatial resolution for diagnosis, mitigate the risk of motion and beam hardening artifacts, and whether these devices could be used in a screening capacity in the horseracing environment remains to be seen [ 7 ]. There have been similar advancements in standing MRI and PET technologies, but operationalizing them as a screening tool in the clinical and commercial setting remains a challenge [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiography plays an important role in the diagnosis of carpal injury but has wellrecognized limitations. For some horses with third carpal bone (C3) fractures (Fx), the poor sensitivity of planar radiography to identify fracture configuration and the full extent of comminution and other injury has been reported [1][2][3][4][5][6][7][8]. Additional views to the standard radiographic series can be useful in some cases including those with suspected sagittal Fx of the radial facet of C3 (RaF) [9], but not all limitations can be overcome.…”
Section: Introductionmentioning
confidence: 99%